An Efficient Synthesis of Pyrroline‐Fused Acridine Derivatives Catalyzed by Silica Sulfuric Acid. (25th April 2014) - Hu, Ming‐Hua; Lin, Wei; Cao, Cheng‐Pao; Huang, Zhi‐Bin; Shi, Da‐Qing
<x xml:space="preserve">Abstract</x> A simple and efficient synthesis of pyrrolo[2, 3, 4‐kl]acridine‐1‐one derivatives via the cascade reaction of isatins with enaminones catalyzed by silica sulfuric acid (SSA) has been established. In this reactions, SSA shows a highly catalytic nature: easy to handle procedure, short reaction time, recycle exploitation, insensitivity to air and moisture, and excellent isolated yields. The catalyst could be recycled at least five times.